ENHANCED CONCEPTUAL UNDERSTANDING OF ELEMENTS AND COMPOUNDS THROUGH THE STAD LEARNING MODEL ASSISTED BY MOCHECLAY MEDIA - Winedar, Ihza Rizky; Widyaputri, Mutya Ardha; Farid, Mohammad Ghufroni; Listiawan, Listiawan; Maryati, Maryati; Natadiwijaya, Ismail Fikri; Sunarti, Sunarti (Universitas Bhinneka PGRI, 2026)
This study aimed to investigate the influence of the Student Teams Achievement Division (STAD) cooperative learning model supported by Mocheclay media on students’ conceptual understanding in science. A quasi-experimental method was employed, utilizing a non-equivalent group design. Participants were selected through purposive sampling, with class VIII F (30 students) assigned as the experimental group taught using the STAD model assisted by Mocheclay, and class VIII H (30 students) as the control group taught through direct instruction. The calculated effect size was 1.23, indicating a strong influence of the STAD model supported by Mocheclay media on students’ scientific conceptual understanding. The experimental group's normalized gain score reached 64%, whereas the control group achieved only 33%. Independent sample t-test results revealed a significant difference in conceptual understanding between students exposed to the STAD-Mocheclay approach and those taught with direct instruction.